BCES Encryption Algorithm (International Journal of Advanced Research in Computer Science, 2017)
A fundamental problem in cryptography is how to communicate securely over an insecure channel. This problem has been there for a long time and has become even more important especially with the proliferation of computers and communication systems. Achieving information and communications security in an electronic society requires a vast array of technical and algorithms, without which the information security objectives deemed necessary cannot be adequately met. For this reason, this paper aims to propose a new algorithm to improve the security level. That is called as BCES algorithm. Thus, the rest of this paper is organized to offer an overview of basic issues of cryptography and describes in detail a new algorithm.Keywords: BCES, encryption, public key, decryption, algorithm, ASCII